Oncocytic Adenoma in a Pediatric Patient: A Case Report and Literature Review - Roberto Paparella; Giulia Bellone; Laura Rizza; Norman Veccia; Gabriele Ricci; Mauro Calvani; Salvatore Scommegna (Endocrines, 2025)
Background: Oncocytic adenomas (OAs) of the thyroid, previously referred to as Hürthle cell adenomas, are uncommon tumors, particularly in pediatric populations, where they represent a minority of thyroid nodules. Due to their rarity and the potential difficulty in distinguishing benign from malignant forms on cytology, these adenomas present unique diagnostic and management challenges. Here, we report a pediatric case of a large OA of the thyroid, managed with surgical resection following inconclusive fine-needle aspiration (FNA) results. Case Presentation: A 13-year-old girl presented with an enlarging thyroid nodule. An ultrasound examination showed a large (26 × 16 mm), solid, isoechoic nodule with a hypoechoic halo. The FNA findings were inconclusive, indicating a follicular neoplasm with oncocytic features, classified as Bethesda IV. The patient underwent a hemithyroidectomy, and a histopathological examination confirmed an encapsulated OA without evidence of capsular or vascular invasion. The postoperative recovery was uneventful, and follow-up assessments showed no recurrence. Conclusions: OAs in pediatric patients are rare and may pose diagnostic challenges. This case highlights the importance of a comprehensive approach, including surgical resection, for definitive diagnoses in cases where FNA results are inconclusive. Further studies are warranted to establish guidelines for the management of oncocytic thyroid neoplasms in pediatric patients, as well as to understand their clinical behavior in this population.